2022
DOI: 10.1590/1807-1929/agriambi.v26n3p190-197
|View full text |Cite
|
Sign up to set email alerts
|

Water restriction in cowpea plants [Vigna unguiculata (L.) Walp.]: Metabolic changes and tolerance induction

Abstract: Global climate change tends to intensify water unavailability, especially in semi-arid regions, directly impacting agricultural production. Cowpea is one of the crops with great socio-economic importance in the Brazilian semi-arid region, cultivated mainly under rainfed farming and considered moderately tolerant to water restriction. This species has physiological and biochemical mechanisms of adaptation to these stress factors, but there is still no clear vision of how these responses can not only allow survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 44 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…Aires et al ( 2022) reported a reduction in stomatal conductance, intracellular CO 2 content, and chlorophyll fluorescence in plants subjected to 1.3 mM SA. Thus, using a dose four times greater than the dose of SA studied by those researchers, it was observed that the reduction in TSS levels may be related to the inhibitory effects of SA on photosynthetic parameters (Melo et al, 2022a).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Aires et al ( 2022) reported a reduction in stomatal conductance, intracellular CO 2 content, and chlorophyll fluorescence in plants subjected to 1.3 mM SA. Thus, using a dose four times greater than the dose of SA studied by those researchers, it was observed that the reduction in TSS levels may be related to the inhibitory effects of SA on photosynthetic parameters (Melo et al, 2022a).…”
Section: Resultsmentioning
confidence: 86%
“…This is most likely due to the fact that SA is a cellular signal that triggers numerous responses that mitigate the negative effects of environmental stresses (Araújo et al, 2018). and Melo et al (2022a) also suggested that cellular protection against free radicals may lead to a reduced response to oxidative stress, which might explain the decrease in stronger enzyme activity observed in attenuator-treated plants under the W50 irrigation regime.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations